2019
DOI: 10.1002/chem.201901678
|View full text |Cite
|
Sign up to set email alerts
|

Murahashi Cross‐Coupling at −78 °C: A One‐Pot Procedure for Sequential C−C/C−C, C−C/C−N, and C−C/C−S Cross‐Coupling of Bromo‐Chloro‐Arenes

Abstract: The coupling of organolithium reagents, including strongly hindered examples, at cryogenic temperatures (as low as −78 °C) has been achieved with high‐reactivity Pd‐NHC catalysts. A temperature‐dependent chemoselectivity trigger has been developed for the selective coupling of aryl bromides in the presence of chlorides. Building on this, a one‐pot, sequential coupling strategy is presented for the rapid construction of advanced building blocks. Importantly, one‐shot addition of alkyllithium compounds to Pd cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 82 publications
0
17
0
Order By: Relevance
“…NHC ligands are strong σ‐donors, which facilitates OA with substrates that are electronically deactivated (i.e., electron‐rich), such as 4‐chloroanisole . We recently reported the first successful Pd‐mediated cross‐coupling at −78 °C, further illustrating this point …”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…NHC ligands are strong σ‐donors, which facilitates OA with substrates that are electronically deactivated (i.e., electron‐rich), such as 4‐chloroanisole . We recently reported the first successful Pd‐mediated cross‐coupling at −78 °C, further illustrating this point …”
Section: Resultsmentioning
confidence: 90%
“…[15] We recently reported the first successful Pd-mediated cross-coupling at À78 8C, further illustrating this point. [37,38] When we lookeda tt he concentration of the amine partner the reactionw as found to be zeroth-orderi no ctylamine suggesting coordination of N-alkylamines to aryl palladium complex 2 is not as ignificant factor in the overall reactionr ate (entries 1, 4a nd 5). In light of the above rate data, this leaves RE (3 to 5)o re ither deprotonation leading to 3 (Figure 1, Path-way I) or one of the steps of the ligand exchange route (Figure 1, PathwayI I) to be rate-determining.…”
Section: Resultsmentioning
confidence: 98%
“…In 2019, Feringa, Organ and co‐workers reported Murahashi cross‐coupling of aryl bromides with alkyl and aryl organolithium reagents catalyzed by Pd‐BIAN‐IPent catalyst 11 (Scheme 12). [46] Interestingly, this catalyst showed higher reactivity than the classical imidazolylidene‐based Pd‐PEPPSI‐IPr, Pd‐PEPPSI‐IPent and Pd‐PEPPSI‐IPent Cl , permitting for the first example of the Murahashi coupling at temperatures below −65 °C. The beneficial effect of the BIAN scaffold was also evident in the efficient cross‐coupling at very low catalyst loading (0.1 mol %).…”
Section: Palladium‐bian‐nhc Complexesmentioning
confidence: 99%
“…With RZnX structured reagents we have argued that LiX has a significant impact on the structure of the organozinc in solution, be it through the formation of zincates and/or alterations in the aggregation state of the organozinc, and this markedly impacts the coupling at the TM stage with our Pd‐NHC (N‐heterocyclic carbene) coupling system. We have shown that Pd‐PEPPSI catalysts are able to couple organolithium reagents at −78 °C, which shows the very high reactivity of these complexes . The corresponding Negishi couplings with otherwise identical substrates and reaction conditions could be done as low as −20 °C, but no lower .…”
Section: Negishi Coupling Of Buznbr With Arylbromides With and Withomentioning
confidence: 87%
“…[6c] With RZnX structured reagents we have argued that LiX has as ignificant impact on the structure of the organozinc in solution, be it through the formation of zincates [4c, 6a,b] and/or alterations in the aggregations tate of the organozinc, [6c] and this markedlyi mpacts the coupling at the TM stage with our Pd-NHC (N-heterocyclic carbene) coupling system.W eh ave shown that Pd-PEPPSI catalysts are ablet oc ouple organolithium reagents at À78 8C, which shows the very high reactivity of these complexes. [10] The correspondingN egishic ouplings with otherwise identical substrates and reactionc onditions could be done as low as À20 8C, but no lower. [8,11] This illustrates that oxidative addition (OA) and reductivee limination (RE) are indeedv ery rapid processes for bulky Pd-PEPPSIc atalysts and suggestst hat the rate-limiting step of the process involves the organometallic partner,a tl east when NHC ligandsa re employed.…”
mentioning
confidence: 99%